Ligneous Conjunctivitis Secondary to Viral Conjunctivitis. Issue 1 (29th January 2023) - Quintero-Estades, Jose A.; Iacob, Codrin E.; Donnenfeld, Eric D.; Perry, Henry D.
Abstract: Ligneous conjunctivitis is a rare cause of chronic conjunctivitis that may be triggered by ocular insults such as trauma or infections. We present an interesting case of ligneous conjunctivitis caused by a viral infection that responded well to conservative management. Topical cyclosporine and heparin are a good treatment regimen that caused resolution of lesions and prevented recurrences.